Facile Synthesis of Hollow Carbon Nanospheres by Using Microwave Radiation - Jiareng Chen; Jiaqi Lin; Bin Cui; Yang Liu (International Journal of Polymer Science)
Carbon-based nanomaterials have attracted much research interest in recent years due to their excellent chemical and physiological properties such as chemical stability, low cytotoxicity, and biocompatibility. The traditional methods to prepare hollow carbon nanospheres require complicated instrumentation and harsh chemicals, including high-temperature furnace, gas inlets, and hydrogen fluoride etching. Herein, we propose a new strategy to prepare hollow carbon nanospheres in a simple and fast manner by using microwave radiation. Polypyrrole-coated silica core-shell nanoparticles (SiO2@PPy NPs) were firstly prepared and subsequently processed by microwave radiation and aqueous alkaline solution to obtain the hollow carbon nanospheres. This facile method has potent potential to be utilized in the preparation of different types of hollow carbon nanospheres with various microstructure and elemental composition.